Mastering Perl - Brian D Foy (Shroff Publishers & Distributors PVT. LTD., 2007)
This is the third in O'Reilly's series of landmark Perl tutorials, which started with Learning Perl, the bestselling introduction that taught you the basics of Perl syntax, and Intermediate Perl, which taught you how to create re-usable Perl software. Mastering Perl pulls everything together to show you how to bend Perl to your will. It convey's Perl's special models and programming idioms.This book isn't a collection of clever tricks, but a way of thinking about Perl programming so you can integrate the real-life problems of debugging, maintenance, configuration, and other tasks you encounter as a working programmer.